KEBIJAKAN AUSTRALIA DALAM MENANGANI IMIGRAN ILEGAL DIBAWAH KEPEMIMPINAN PERDANA MENTERI TONY ABBOTT TAHUN 2013 - Ardianti " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes about Australia’s policy to control the illegal immigrants in 2013. In particular, this research describes the policies adopted by Prime Minister Tony Abbott. Australia is a country which to be one of the international immigrant. The Increased arrivals of illegal immigrants from year to year make impact to sovereignty and security of Australia region. Therefore, it requires the government to be firm in handling it. The concept that used by author is national interest by Morgenthau, realis approach and securitization theory by Barry Buzan. The theory and concept use to understand the policy of Australian government to protect the sovereignty of Australian territory from the transnational crime. The result of this research is the policies adopted by prime minister Tony Abbott to control the arrival of the illegal immigrants is the policy of Operation Sovereign Borders (OSB). OSB done by placing Austalian militery in border area to prevent the arrival of illegal immigrants or asylum seeker by boat. OSB policy implementation in the field is to intercept or repatriate back boats carrying asylum seekers to the embarkation country.Keywords: Policy, Illegal Immigrant, Asylum Seeker, Operation Sovereign Borders (OSB)